"Leveraging blockchain-based financing mechanisms for carbon sequestration and biodiversity enhancement." A feasibility study - Sven Heinrichs; Franz Isselstein (IU Internationale Hochschule, 2024)
Climate change exists and poses a great threat to all living beings on our planet. Any further delay in global action on mitigation will make it more difficult to secure a liveable and sustainable future for all. In this exploratory study, an inductive approach based on qualitative evidence from expert interviews as well as literature is applied to assess the economic feasibility of ecologically enhancing unused land with an initial focus in Germany and using the so far limited financing potential of blockchain token to incentivize project participation and let investors earn sustainable returns from carbon sequestration and probable future biodiversity rewards. Security token offerings can be a valuable alternative for business and project financing. Tokenization reduces transaction costs through automation and disintermediation, supporting transparency and liquidity. The creation of agroforestry systems can serve as an effective way to benefit the environment as well as agriculture. Private funding initiatives are highly demanded for such activities as government subsidies diminish. Financial modelling shows that under the given assumptions the project can be economically feasible, providing returns comparable to benchmarks for agriculture investments and a positive Net Present Value. However, the expert interviews show, that the lease model / user right schematic should not be neglected and needs to be investigated further as it promises highly promising results.
Keywords: Q57; Q52; Q58; G23; O31; Q01; 650; Carbon Sequestration; Security Token; Security Token Offering; Blockchain; climate finance; HedgeToken